Use of the “DNAChecker” Algorithm for Improving Bioinformatics Research - Bhat, Nausheen; Wijaya, Ezra Bernadus; Parikesit, Arli Aditya (UI Scholars Hub, 2019)
Basic Local Alignment Sequencing Tool (BLAST) is a bioinformatics tool used for analyzing nucleotide sequences with regards to their similarity. BLAST can be found online on biological databases such as the National Center for Biotechnology Information (NCBI) and other such repositories. The mechanism of BLAST allows the target sequence to be compared with other sequences to find regions of local similarity, and thus, a comparability quotient that determines the resemblance between the sequences is created. Due to the open-platform nature of the online databanks, several sequences can be accepted with little to no interjections regarding the quality of sequence submitted. An example of unclean nucleotide sequences can be based on the number of non-template nucleotides, denoted as “N,” present within the sequence. Here we develop a self-established nucleotide sequence reading program known as “DNAChecker,” which helps identify the quality of the target sequence and therefore proposes the effectiveness of the BLAST result. DNAChecker is an inbuilt, program that runs on Python 3.4 and was implemented in the United States Agency for International Development (USAID) project conducted in Indonesia International Institute for Life Sciences. Although DNAChecker has proven to be useful, it has a lot of room for improvements, such as having a more objectively accurate means of differentiating between good and bad sequences.